The Morphological Roots of "Hazm " in the Arab Dictionary - AL-Hashmawei, Madhoor Mahmood (Journal of Tikrit University for Humanities, 2023)
Derivation is a significant linguistic phenomenon, particularly in the context of the Arabic language. The Arabic language is known for its derivational nature, which contributes to its sophistication, brilliance, and distinctiveness compared to other languages. Derivation involves the alteration of a word's final condition in terms of its meaning and structure, resulting in a distinct formula. Both ancient and contemporary Arabic scholars have devoted considerable attention to the concept of derivation. However, they have held differing views regarding its origin. The Basranians, for instance, believed that the infinitive serves as the fundamental source, while some ancient scholars, such as those from Kufa, argued that the verb itself is the origin. Another group of scholars contended that the root, also known as the "raw material," is the true origin of derivation. Ancient Arabic scholars demonstrated a keen interest in the study of derivation and derivatives within their linguistic works, particularly in the realm of dictionaries. This scholarly pursuit can be traced back to Al-Khalil and continued through subsequent dictionaries, showcasing the evolution and rejuvenation of the Arabic language. Notably, Arabic scholars emphasized the significance of the root, which served as the fundamental building block in their approach to the organization and structure of words. The morphological derivations of the root "hazim" in Arabic dictionaries exhibit variation in terms of the structures employed, encompassing both abstract and augmented verbs, as well as nouns. These derivations encompass subjective nouns, infinitives denoting meaning, derivations from the name of the subject, modal adjectives, nouns denoting instruments, and plurals denoting the act of crushing.